2018
DOI: 10.1029/2018gl078040
|View full text |Cite
|
Sign up to set email alerts
|

An Increase of the Indonesian Throughflow by Internal Tidal Mixing in a High‐Resolution Quasi‐Global Ocean Simulation

Abstract: The impact of internal tidal mixing on the volume transport of the Indonesian Throughflow (ITF) is examined by a comparison of high‐resolution quasi‐global ocean simulations with and without a tidal mixing scheme. The ITF transport is found to be increased in the presence of tidal mixing. This is because tidal mixing decreases the density within and below the lower thermocline and increases the buoyancy of the water column. As a result, the surface pressure and the sea surface height (SSH) are raised. The magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 40 publications
3
20
0
Order By: Relevance
“…6d), the fresher bias (< -0.2 psu) spreads from the western Pacific into the Celebes Sea, gradually weakens southward, and disappears at the Makassar Strait. The saltier bias (> 0.3 psu) spreads to the south of Java and the Sunda Islands, which decreases to approximately 0.2 psu along approximately 12° S. The cause of these biases may be partially due to the lack of nonlocal tidal mixing (e.g., Nagai et al, 2017), as discussed in a study by Sasaki et al (2018). The impact of nonlocal tidal mixing is an interesting subject for a future study.…”
Section: Impact Of Tidal Mixing On Water Mass Propertymentioning
confidence: 89%
See 1 more Smart Citation
“…6d), the fresher bias (< -0.2 psu) spreads from the western Pacific into the Celebes Sea, gradually weakens southward, and disappears at the Makassar Strait. The saltier bias (> 0.3 psu) spreads to the south of Java and the Sunda Islands, which decreases to approximately 0.2 psu along approximately 12° S. The cause of these biases may be partially due to the lack of nonlocal tidal mixing (e.g., Nagai et al, 2017), as discussed in a study by Sasaki et al (2018). The impact of nonlocal tidal mixing is an interesting subject for a future study.…”
Section: Impact Of Tidal Mixing On Water Mass Propertymentioning
confidence: 89%
“…Sensitivity experiments are becoming more feasible. Sasaki et al (2018) showed that the inclusion of a tidal mixing scheme can result in an enhancement in ITF transport due to the basin-scale SSH increase in the tropical Pacific Ocean. While the direct impact of tidal mixing is local, its impact appears to spread over a whole basin via Rossby and Kelvin waves (Furue et al 2015).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…OFES2 is a quasi‐global general circulation model that has a spatial resolution of 0.1° and is an update of OFES (Masumoto et al, ; Sasaki et al, ), which now includes a global tidal mixing parameterization. Readers are referred to Sasaki et al () for model details. The 22‐year monthly averaged OFES2 outputs are used to estimate the monthly climatologies, which are then used for the analysis unless noted otherwise.…”
Section: The Model Setupmentioning
confidence: 99%
“…In order to estimate the trajectories of the Lagrangian particle tracking model, we use OFES2 from 1995 to 2016 (Sasaki et al, 2018). OFES2 is a quasi-global general circulation model that has a spatial resolution of 0.1°and is an update of OFES (Masumoto et al, 2004;Sasaki et al, 2008), which now includes a (Boyer et al, 2013), and red lines are from OFES2.…”
Section: Ofes2 Model Outputmentioning
confidence: 99%
See 1 more Smart Citation